2015
DOI: 10.20882/adicciones.695
|View full text |Cite
|
Sign up to set email alerts
|

Exposición a tabaco, alcohol y drogas de abuso en gestantes. Estudio de prevalencia en gestantes de Málaga (España)

Abstract: The prevalence of substance abuse in women who become pregnant is similar to that of the general population, resulting in a high fetal exposure rate during the most vulnerable period regarding neurodevelopment and organogenesis. The present study was intended to assess the level of prenatal exposure to tobacco, alcohol or illicit drugs in the city of Málaga (Spain). It was designed as a cross-sectional study, and based on the anonymous self-reports of participants. A total of 451 pregnant women were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
3
0
4
Order By: Relevance
“…Our data showed that only having a primary level education was more common in cannabis users, both in mothers and fathers alike, in agreement with other studies [64,65]. The association between alcohol consumption and a higher academic level has been described previously [60]. In our study, an association was found between fathers with a bachelor's degree and a higher frequency of alcohol consumption, although no differences were found in mothers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showed that only having a primary level education was more common in cannabis users, both in mothers and fathers alike, in agreement with other studies [64,65]. The association between alcohol consumption and a higher academic level has been described previously [60]. In our study, an association was found between fathers with a bachelor's degree and a higher frequency of alcohol consumption, although no differences were found in mothers.…”
Section: Discussionsupporting
confidence: 93%
“…The average age of mothers that were included in our study (32.4 years) was similar to that previously reported in the international literature [37,42,58,60]. Psychoactive substance use was significantly associated with younger age, as reported in other studies [42].…”
Section: Discussionsupporting
confidence: 86%
“…La ocurrencia del consumo de alcohol en esta muestra de mujeres embarazadas y lactantes fue notablemente inferior a la reportada en trabajos locales previos (5) y de otros países (4,(15)(16)(17)(18). En general, observamos un perfil más riesgoso en mujeres lactantes.…”
Section: Discussionunclassified
“…Hasta donde sabemos, no hay datos representativos a nivel nacional en España. En un estudio realizado en Málaga con 451 mujeres embarazadas, el 27,5% admitió haber bebido durante el embarazo (Blasco-Alonso et al 2015). Tampoco en Portugal hay información representativa nacional, aunque en un trabajo realizado por nuestro equipo portugués en este estudio encontró una indicación de consumo durante la gestación del 20,3% de las mujeres embarazadas (N=369) en una muestra nacional recolectada en línea (Xavier et al, 2019).…”
Section: Introductionunclassified